Association between Placental Lesions, Cytokines and Angiogenic Factors in Pregnant Women with Preeclampsia - Weel, Ingrid C. [UNESP]; Baergen, Rebecca N.; Romao-Veiga, Mariana [UNESP]; Borges, Vera T. [UNESP]; Ribeiro, Vanessa R. [UNESP]; Witkin, Steven S.; Bannwart-Castro, Camila [UNESP]; Peracoli, Jose C. [UNESP]; De Oliveira, Leandro [UNESP]; Peracoli, Maria T. [UNESP] (Public Library Science, 2016)
Preeclampsia (PE) is considered the leading cause of maternal and perinatal morbidity and mortality. The placenta seems to play an essential role in this disease, probably due to factors involved in its formation and development. The present study aimed to investigate the association between placental lesions, cytokines and angiogenic factors in pregnant women with preeclampsia (PE). We evaluated 20 normotensive pregnant women, 40 with early-onset PE and 80 with late-onset PE. Placental samples were analyzed for histopathology, immunohistochemistry and determination of granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin-10 (IL-10), transforming growth factor-beta 1 (TGF-beta 1), tumor necrosis factor-alpha (TNF-alpha), placental growth factor (PlGF), vascular endothelial growth factor (VEGF), fms-like tyrosine-kinase-1 (Flt-1) and endoglin (Eng) levels. Higher percentages of increased syncytial knots and increased perivillous fibrin deposits, and greater levels of TNF-alpha, TGF-beta 1 and Flt-1 were detected in placentas from early-onset PE. Levels of IL-10, VEGF and PlGF were decreased in PE versus normotensive placentas. Both the TNF-alpha/IL-10 and sFlt-1/PlGF ratios were higher in placental homogenate of early-onset PE than late-onset PE and control groups. The more severe lesions and the imbalance between TNF-alpha/IL-10 and PlGF/sFlt-1 in placentas from early-onset PE allows differentiation of early and late-onset PE and suggests higher placental impairment in early-onset PE.